Smartphone Video Education-Based Diaphragmatic Respiratory Intervention As An Effort To Improve The Comfort Of Breast Cancer Patients Who Undergoing Chemotherapy At Arifin Achmad Hospital Riau Province - Defi Eka Kartika; Rosyadi, Imran; Sandra; Noviyani, Dwi; Veralia; Yolanda, Martha (Infomasi dan Promosi Kesehatan, 2024)
Chemotherapy drugs have a systemic effect that can kill cancer cells as well as healthy cells, causing discomfort to breast cancer patients due to the side effects of the treatment. One of the non-pharmacological treatments to reduce the symptoms of discomfort in breast cancer patients undergoing chemotherapy is diaphragmatic breathing which has benefits for mental and physical health. This study aims to determine the effect of diaphragmatic breathing intervention based on smartphone video education as an effort to increase the comfort of breast cancer patients undergoing chemotherapy. This research uses a Quasy Experiment With Pre-Test-Post-Test design. Diaphragmatic breathing exercise intervention was carried out for 10 minutes with a frequency of 3 times a day until day 7 after chemotherapy. Data were analyzed using the Wilxocon test. The research results in this study show the influence of diaphragmatic breathing exercises on the comfort of breast cancer patients undergoing chemotherapy. Conclusion: nurses are advised to educate breast cancer patients undergoing chemotherapy to carry out this intervention while at home.